A Constructivist Vision of the First-Trimester Abortion Experience - Sam Rowlands; Jeffrey Wale (Harvard FXB Center for Health and Human Rights, 2020)
How might the abortion experience look in a world without the existing regulatory constraints? This paper critically assesses the evidence about how a high-quality abortion experience might be achieved in the first trimester. There would need to be positive obligations on states in pursuance of women's reproductive rights. The onus would be on states and state actors to justify interferences and constraints upon a woman's right to terminate in the first trimester of her pregnancy. In this vision, abortion is person-centered and normalized as far as possible. High-quality information about abortion would be freely available through multiple sources and in varying formats. Whenever possible, abortion would happen in a place chosen by the woman, and in the case of medical abortion, could be self-managed with excellent clinical backup on hand should the need arise. The overarching purpose of this paper is to highlight the broader environment and framework of state obligations necessary to underpin the lived experience of abortion.